Meaning of Phrasal Verb ‘Pick up’ Subtype Do/Happen: A Natural Semantic Metalanguage Approach - Inten Purnama Sari Setiawan, Luh Gede (e-Journal of Linguistics; Vol 13 No 2 (2019): e-jl-JulyDO - 10.24843/e-JL.2019.v13.i02.p13, 2019)
The difficulties in knowing and understanding the meaning of a language often appear in units of language with an idiomatic meaning, such as phrasal verb. A single unit of phrasal verb usually produce a meaning which is totally different with the meaning of its constituent. Phrasal verb ‘pick up’ is a unique phrasal verb since it is able to give various meanings unlike the other phrasal verbs. Furthermore, the implementation of Natural Semantic Metalanguage (NSM) as a theory in this study lead to a great significance in order to avoid misunderstanding the meaning of phrasal verb ‘pick up’ by defining the meaning through semantic structures. This study is intended to find and describe the meanings of phrasal verb ‘pick up’. The result of this study showed that phrasal verb pick up is a kind of transitive phrasal verb which often followed by object. The different objects in phrasal verb ‘pick up’ lead to non-composition polysemi between DO / HAPPEN. This combination of two polysemies comes in eight meanings.